Susceptibility of Euschistus heros (Fabricius, 1798) (Hemiptera: Pentatomidae) nymphs to Bacillus spp. strains - Castro, Marcelo T. de; Gomes, Giovana C.; Cunha, Breno B. dos R.; Rocha, Gabriela T.; Ferreira, Antônia D. C. de L.; Montalvão, Sandro C. L.; Monnerat, Rose G. (Entomological Communications, 2025)
Soybean crops are subject to various phytophagous insects, among which the Neotropical brown stink bug Euschistus heros (Fabricius, 1798) (Hemiptera: Pentatomidae) stands out. The biological control of this pest is one of the viable alternatives to reduce the use of chemical insecticides. This study aimed to evaluate the pathogenic potential of different Bacillus spp. strains in the mortality of nymphs of E. heros under laboratory conditions. Bioassays were done using the artificial feeding system methodology with Falcon tubes, and seventeen Bacillus spp. strains were utilized. As a result, one strain of Bacillus thuringiensis caused 100% mortality, and the lethal concentration (LC₅₀) was estimated: 8.42 × 10⁴ spores/mL. In addition, two other strains of B. thuringiensis and one strain of Bacillus cereus caused mortality above 70%, and a Bacillus velezensis caused 55%.